2019
DOI: 10.1080/15592324.2019.1657343
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidases, essential players of hormone signalings in plant development and response to stresses

Abstract: Plasma membrane NADPH oxidases (NOXs), also named respiratory burst oxidase homologues (Rbohs), are critical generators of reactive oxygen species (ROS), which as signal molecules regulate growth and development, and adaptation to various biotic and abiotic stresses in plants. NOXs-dependent ROS production is frequently induced by diverse phytohormones. The ROS commonly function downstream of, and interplay with hormone signalings, coordinately modulating plant development and stress tolerance. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…The available RNA-seq data showed that CsRbohE , clustered in the same group 1 as the AtRbohD gene, was highly expressed in all four tissues ( Figure 5 ). Again, the homologous gene AtrbohD was expressed in all tissues of Arabidopsis and was involved in many physiological processes such as stomatal closure, root formation, and systemic signaling in response to diverse stresses [ 1 , 30 ]. Therefore, we speculate that CsRbohE may have a similar function to AtRbohD .…”
Section: Discussionmentioning
confidence: 99%
“…The available RNA-seq data showed that CsRbohE , clustered in the same group 1 as the AtRbohD gene, was highly expressed in all four tissues ( Figure 5 ). Again, the homologous gene AtrbohD was expressed in all tissues of Arabidopsis and was involved in many physiological processes such as stomatal closure, root formation, and systemic signaling in response to diverse stresses [ 1 , 30 ]. Therefore, we speculate that CsRbohE may have a similar function to AtRbohD .…”
Section: Discussionmentioning
confidence: 99%
“…•− -generating NOX during sweet pepper fruit ripening should be also integrated with the NADPH-generating system constituted by a group of NADP-dehydrogenases, which are regulated by signal molecules such as NO and H 2 S (Muñoz-Vargas et al, 2018. Additionally, future analyses should be developed to understand the integration of the redox homeostasis with the phytohormones including ABA, indole-3-acetic acid, gibberellins, cytokinins, or jasmonic acid involved in the ripening of sweet pepper considering that it is a non-climacteric fruit (Symons et al, 2012;Fuentes et al, 2019;Sun et al, 2019). This will allow to extend our knowledge of the complex network of involved signal molecules in this physiological process.…”
Section: Discussionmentioning
confidence: 99%
“…After imbibition, the resurgence of mitochondrial respiration in the seed may cause electrons to be donated to oxygen as an electron acceptor, leading to ROS production ( Kranner et al, 2010 ). NADPH oxidases, also known as respiratory burst oxidase homologs (Rbohs) after the homology with gp91 phox domain of the mammalian respiratory burst oxidase are main drivers of ROS production in the cell wall space which leads to seed germination through non-enzymatic way and results in radicle elongation and endosperm cap weakening in dicots ( Sun L. R. et al, 2019 ). Rbohs transfers the electron from NADPH or NADH to apoplastic oxygen which results in the production of superoxide radicals and these radicals can directly cleave polysaccharides which will loosens the plant cell walls ( Yang et al, 2020 ).…”
Section: Role Of Reactive Oxygen Species In Seed Germinationmentioning
confidence: 99%